Persepsi Penggunaan Qris Sebagai Alat Pembayaran Pada Umkm Di Bengkulu: Analisis Peran Administrasi Publik Dalam Mendorong Digitalisasi Ekonomi - Holida , Meylinda (CV. ITTC INDONESIA, 2024)
This study aims to analyze the perception of using the Quick Response Indonesian Standard (QRIS) as a payment tool among Micro, Small, and Medium Enterprises (UMKM) in Bengkulu, as well as the role of public administration in promoting economic digitalization. The method employed is a qualitative descriptive study, with data collected through in-depth interviews and participatory observations. The findings indicate that the perception of UMKM actors towards QRIS is generally positive, with many experiencing convenience and efficiency in transactions. However, challenges such as limited internet access and a lack of understanding of digital technology remain significant obstacles. Public administration plays a crucial role in creating policies that support QRIS adoption, including infrastructure improvement and digital literacy programs. This study recommends the need for collaboration between the government, private sector, and society to optimize the potential of the digital economy, enabling UMKM to compete more effectively in an increasingly digital marketplace.